Proceedings of the Unima International Conference on Social Sciences and Humanities (UNICSSH 2022) 2023
DOI: 10.2991/978-2-494069-35-0_48
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Socio Economic Parent on Using Digital Media in Early Childhood

Abstract: Technological advancements entering the industrial era 4.0 bring changes to all aspects of human life including children especially in their use of social digital media. This study aims to examine the effect of parents' education level and economic level on their children's use of digital media in early childhood. In this quantitative research, an online questionnaire bundle Surveillance of Digital Media habits in Early Childhood Questionnare (SMALLQ) was employed to measure the digital literacy of parents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Soltani et al (2016) showed that the quantity and quality of mothers' media use with their 4 to 7year-old children are related to the children's lesser use of certain media (Soltanal-Qara'ee & Mola Ghalghachi, 2015). Fauziah et al (2023) demonstrated that the required level of technology literacy among parents could regulate children's digital consumption in selecting media content and tools. Brohl et al (2013) found that providing media literacy education to mothers under the supervision of the Canadian Public Health Organization has led to meaningful and purposeful use of media in children (Fauziah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Soltani et al (2016) showed that the quantity and quality of mothers' media use with their 4 to 7year-old children are related to the children's lesser use of certain media (Soltanal-Qara'ee & Mola Ghalghachi, 2015). Fauziah et al (2023) demonstrated that the required level of technology literacy among parents could regulate children's digital consumption in selecting media content and tools. Brohl et al (2013) found that providing media literacy education to mothers under the supervision of the Canadian Public Health Organization has led to meaningful and purposeful use of media in children (Fauziah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Fauziah et al (2023) demonstrated that the required level of technology literacy among parents could regulate children's digital consumption in selecting media content and tools. Brohl et al (2013) found that providing media literacy education to mothers under the supervision of the Canadian Public Health Organization has led to meaningful and purposeful use of media in children (Fauziah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effective integration of educational technologies into early childhood education remains a significant challenge, requiring careful consideration of pedagogical practices and the impact of digital technologies on children's learning and development (Vidal-Hall et al, 2020). The influence of socio-economic factors on children's use of digital media in early childhood has also been investigated, emphasizing the need to address disparities in access to digital technologies among young children (Fauziah et al, 2023).…”
Section: The Intersection Of Digital Age Challenges and Early Life Tr...mentioning
confidence: 99%